CRIMINAL CODE BILL ARTICLE 414 AND SEX EDUCATION IN INDONESIA - Maddussila, Samsu Alam (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
Sex education in Indonesia still taboos to talk in an educational context; however, sexual abuse, free sex, and abortion are increasing more and more. This situation more likely will get in an emergency when criminal code bill article 414 about showing contraception tools to children is applied because it is considered cut off sexual education teaching and against HIV/AIDS and family planning campaign.Â This article focuses on analyzing criminal code bill article 414 toward sex education in Indonesia and discussing possible solutions for including sex education in the school curriculum. Several critics addressed in criminal code article 414, and several solutions were given in this article for including sex education in the Indonesian curriculum. There is some limitation occurred toward this article, especially, the literature which addressed this issue is limited. In addition, it seems the experts are not discussing about this issue regularly.